H4K20 monomethylation inhibition causes loss of genomic integrity in mouse preimplantation embryos - Daiki SHIKATA; Takuto YAMAMOTO; Shinnosuke HONDA; Shuntaro IKEDA; Naojiro MINAMI (The Society for Reproduction and Development, 2020)
Maintaining genomic integrity in mammalian early embryos, which are deficient in DNA damage repair, is critical for normal preimplantation and subsequent development. Abnormalities in DNA damage repair in preimplantation embryos can cause not only developmental arrest, but also diseases such as congenital disorders and cancers. Histone H4 lysine 20 monomethylation (H4K20me1) is involved in DNA damage repair and regulation of gene expression. However, little is known about the role of H4K20me1 during mouse preimplantation development. In this study, we revealed that H4K20me1 mediated by SETD8 is involved in maintaining genomic integrity. H4K20me1 was present throughout preimplantation development. In addition, reduction in the level of H4K20me1 by inhibition of SETD8 activity or a dominant-negative mutant of histone H4 resulted in developmental arrest at the S/G2 phase and excessive accumulation of DNA double-strand breaks. Together, our results suggest that H4K20me1, a type of epigenetic modification, is associated with the maintenance of genomic integrity and is essential for preimplantation development. A better understanding of the mechanisms involved in maintaining genome integrity during preimplantation development could contribute to advances in reproductive medicine and technology.